Ambulatory care sensitive hospitalizations after implementation of the master plan in Minas Gerais - Luciano José Arantes; Helena Eri Shimizu; Edgar Merchán-Hamann (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To describe the rate of ambulatory care sensitive hospitalizations in groups of cities according to population size and to analyze its association with the coverage of the Family Health Strategy after the implementation of the Master Plan for Primary Health Care in Minas Gerais, Brazil. METHODS This is an ecological study with 452 cities grouped according to population size, with data from 2004 to 2007 and 2010 to 2013. We used the Kolmogorov-Smirnov test to verify the distribution of the data in the groups. We used the Wilcoxon test for paired data or the paired Student's t-test to compare the rate of ambulatory care sensitive hospitalizations before and after the Master Plan for Primary Health Care. We used the simple linear regression test to analyze the association between variables. We performed statistical analyses using the Statistical Package for the Social Sciences, with a significance level of 5%. RESULTS The rate of ambulatory care sensitive hospitalizations decreased significantly after the Master Plan for Primary Health Care in the large and mid-sized groups (p < 0.05). There were positive correlations between coverage with Family Health Strategy and the rate of ambulatory care sensitive hospitalizations in the mid-sized and large groups (p < 0.05). CONCLUSIONS Actions were carried out to implement the Master Plan for Primary Health Care. However, more investments are needed to improve the effectiveness of the Primary Health Care, with permanent confrontation of complex issues that affect the quality of services, which can lead to a significant reduction of the rates of ambulatory care sensitive hospitalizations.